(3GdHjGf hGdJMUjd aj abg GdeGdcjgs - (3eMeO Hf CMeO Hf CMeO Hf QTO GdeGdcj GdbQWHj GdCfOdSj, GdbGVj CHh GdhdjO (B( (3GdLO (B)(3, J (B520 (3g` s
(3ChdgG (B:s
(3cJGH GdLfGFR ef SeGY GHf GdbGSe ef cJGH GdQWH HGdjGHS bGd SMfhf bGd SFd eGdc Yf fRY GdCQOjI ai GdLfGFR bGd HFS GdYed s
(3BNQgG (B:s
(3bGd GdEeGe GdbGVi EfeG JLhR UObJg hYJbg ef QCS eGdg Je cJGH GdLgGO jJdhg Ef TGA Gddg JYGdi ef SeGY GHf GdbGSe ef cJGH GdQWH HGdjGHS s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B313s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: 749s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdeGdcjs